The importance of entrepreneurship foundation knowledge for sustainable growth: a case study of street food microenterprise at Kota Bharu - Wan Hasnan Wan Idris (2021)
The aim of this study is to identify the importance of entrepreneurial foundation knowledge to the microenterprise for sustainable growth and to analyze what critical factors can motivate and influence microenterprise to grow their business. The conceptual model is based on Resource-Based View (RBV) of entrepreneurial foundation knowledge which emphasized on knowledge on product and development, sales and marketing, management and finance. The result of this study provides some insights to business practitioners and policymakers to address the determinants pertaining to microenterprise growth to the next level